Penerapan Model Explicit Intruction untuk Meningkatkan Keterampilan Pemahaman Konsep IPA Siswa SD Negeri 0602 Matondang - Rumonda Daulay; Era Mutiah; Nurhalimah Harahap (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2026)
Based on observations that have been made at SD Negeri 0602 Matondang there are problems in science learning, the problem is that students do not pay attention to the teacher’s explanation in each lesson, the learning process in class the teacher applies the lecture and question and answer method only so that it makes students bored, the results of student report cards in odd semesters have not reached KKM. The purpose of this study was to determine the comprehension skills of SD Negeri 0602 Matondang students about the concept of science on the application of the Explicit Instrument learning model, to determine the level of comprehension skills of SD Negeri 0602 Matondang students about the concept of science on the application of the Explicit Instrument learning model. The method carried out in this study is Classroom Action Research (PTK). The comprehension skills of grade V students of SD Negeri 0602 Matondang improved significantly obtained data from 20 students. In the pre-cycle there are 25% of students who have the category of understanding the concept of science "Good". Meanwhile, in the first cycle, data were obtained on 60% of students who had the category of understanding the concept of science "Good". In cycle II, data was obtained to 90% of students who had the category of understanding the concept of science "Good". The application of this learning model is important for students because having time to practice better and emphasized gradually or step by step is very well applied in declarative or procedural learning knowledge.